Implementación del sistema de gestión de salud y seguridad en el trabajo para la empresa Ingenia Colombiano Ingco S.A.S. con base al decreto 1072 de 2015 (2017)
The implementation of the Occupational Health and Safety Management System is implemented based on Decree 1072 of 2015 in Ingenio Colombiano INGCO SAS, as a strategic project to comply with the mandatory compliance legislation in Colombia, as well as ensuring that the safety and health of workers is important and create a culture of self-care; In order to achieve this, the design, execution and evaluation of the SGSST is carried out. In the long term, INGCO will obtain intangible benefits such as improving conditions and jobs place, increasing productivity, providing workers with a healthy, pleasant free and organized environment, demonstrating credibility and providing confidence to customers.